Improvement Design of Packaged Juice Production Process using Business Process Reengineering - Novandra Rhezza Pratama; Putri Amaliyah Agustin (International Journal of Technology)
Process efficiency is required in packaged juice production to meet the greater demand for its product. The manual production process causes time loss, poses a bottleneck, and results in waste due to the time-consuming process. This study aims to design an improvement in the production process of packaged juice by eliminating the waste that occurs to increase the productivity and efficiency of processing. Process Activity Mapping and Waste Assessment are used to map the activities and identify waste. The improvement design is executed using a Business Process Reengineering (BPR) through implementing a combination of BPR best practices and simulation using iGrafx software. Process improvement involves the entire production process that consists of three stages, namely the puree-making stage, production stage, and packaging stage. This research resulted in designs of improvement solutions. The models of the improvement solutions are then simulated and produce an improved production process time. This solution resulted in a 34.9% reduction in distance traveled and a 50.54% reduction in total processing time.